Orthopedic Treatment of Clavicle Fracture in Adulthood at Sylvanus Olympio Teaching Hospital of Lome (Togo): Functional and Anatomical Results - Ananivi Sogan; Efoe-Ga Amouzou; Yaovi Dellanh; Komlan Adabra; Anani Abalo; Assang Dossim (European Scientific Journal, ESJ, 2018)
Background: Fractures of the clavicle are relatively frequent and are benign lesions. Their management may be nonoperative or surgical. The objectives of this study were to determine the functional and anatomical outcome of fractures of the adult clavicle after nonoperative treatment. Materials and methods: Two years retrospective study was done. It rolled patients with clavicle fracture treated with either plaster bolero, scarf or clavicular brace with or without rehabilitation, who gave informed consent and who agreed to provide us initial and control radiological pictures. The objective results were evaluated by the Constant score and radiological control images. The subjective results were mainly represented by the impressions of the patients. Results: We recorded 171 cases of clavicle fracture in adults, or 6.2% of fractures in general, including 53 women. The sample studied consisted of 114 cases, including 12 women. In the majority of cases the constant score was either good, 65.8% or excellent, 20.7%. We have not noticed a poor result. Radiologically, the evolution was marked by 90.4% of vicious callus and 2.6% of pseudarthrosis. More than half of the patients, 62.2% were satisfied with the results of the nonoperative treatment received. Conclusion: The evolution of the fractures of the clavicle after nonoperative treatment was therefore favorable on the functional level but marked by vicious callus and pseudarthrosis.